Study Analysis Of Parents' And Teachers' Perceptions Regarding The Cognitive Development Of Early Children In The Areas Of Reading, Writing And Numeration - K, Kisno.; Fatmawati, Nia (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
This research is motivated by the need to analyze the extent to which parents and teachers perceive early childhood cognitive development in the realm of reading, writing and nu-meracy. The purpose of this study is to describe how perceptions, practices, constraints, and things needed by parents and teachers in developing cognitive learning. Initial percep-tions embedded in parents and teachers regarding children's cognitive development will be analyzed as needed and become initial research data for the development of cognitive learning models in the following year. The research was conducted in Bandar Lampung Kindergarten, Enggal District, with 17 teachers and 31 parents as subjects. The sampling technique was randomized. Data were collected through interviews and questionnaires. The research data were analyzed through qualitative and quantitative analysis. The results showed that the level of perception of parents and teachers about children's cognitive development was high, namely 28 people with an interval of 123-159. For the other 11 people, very high with an interval of 16-196, quite high as many as 9 people with an inter-val of 86-122 and no parents and teachers with low levels of perception. Based on the results of the study it can be concluded that the perception of parents and teachers about children's cognitive development generally reaches a high level, therefore this understand-ing can be used as an initial capital in the process of developing children's potential to be maximized.